การวิเคราะห์ปริมาณโซเดียม โพแทสเซียม แคลเซียม และเหล็ก ในน้ำพริกหนุ่มที่จำหน่ายในตลาดสดเขตเทศบาลนครเชียงใหม่ - สิริพริมา วิภาธวัชชัยพร (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The purpose of this independent study was to analyze the quantity of sodium, potassium calcium and iron in Nam PrikNum soldin all markets in Chiang Mai municipal(14 markets).The samples weretwo types of Nam PrikNum included, fresh(in plastic bag) and sealed container(in glass bottle). Each sample ofNam PrikNum was collected 3 times (each time was collected one week apart). The Composite Sample method was used for preparation the two types of NamPrik Num. According to this method, there were 12 fresh samples and 5 sealed container samples per each time of collection.Thus, the total samples were 51 samples.All samples were digested bywet digestion method. After that, all digested samples were analyzed for determining thequantity of the minerals by Atomic Absorption Spectrophotometer (AAS). Descriptive statisticswas used to analyze the data.Theywere average, standard deviation, One-way ANOVA and Independent t-test. The result showed thatthe average amount of minerals in fresh samples from all markets were 1,092.12, 283.05, 25.58 and 1.47 mg. per 100g. for sodium, potassium, calcium, and iron respectively. The average amount of minerals in sealed container samples from all markets were 940.66, 261.28, 18.18 and 1.01 mg. per 100g. for sodium, potassium, calcium, and iron respectively. It was found that fresh samples had the quantity of sodium, potassium and calcium more than those in sealed container samples significant differences at the level ofP<.01 (sodium and calcium) and P <.05(potassium) but they did not showed any significant difference for iron concentration.